2020
DOI: 10.1029/2019ja027488
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Source Region of Whistler Mode Waves in Magnetosheath Mirror Structures

Abstract: In the magnetosheath, intense whistler mode waves, called "Lion roars," are often detected in troughs of magnetic field intensity in mirror mode structures. Using data obtained by the four Magnetospheric Multiscale (MMS) spacecraft, we show that reversals of gradient of magnetic field intensity along the magnetic field correspond to reversals of the field-aligned component of Poynting flux of whistler mode waves in the troughs. Such a characteristic is consistent with the idea that the whistler mode waves are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 128 publications
4
34
2
Order By: Relevance
“…These structures were first identified in the solar wind (Turner et al, 1977), and were subsequently observed frequently in the planetary magnetosheath (e.g., Cattaneo et al, 1998; Balikhin et al, 2009; Tsurutani et al, 2011; Yao ST et al, 2017), in the magnetotail (e.g., Ge YS et al, 2011; Yao ST et al, 2016; Zhang XJ et al, 2017), in the magnetospheric cusp (Shi QQ et al, 2009; Jasinski et al, 2017), and even in the magnetosphere of comets (Russell et al, 1987; Plaschke et al, 2018). They have been identified under various names according to their generation mechanisms and property features, for example, “magnetic dips”, “magnetic decreases”, “mirror modes”, and “solitary waves” (e.g., Song P et al, 1992, 1994; Baumgärtel, 1999; Lucek et al, 1999; Horbury et al, 2004; Stasiewicz, 2004; Tsurutani et al, 2011; Yao ST et al, 2018b; Tian AM et al, 2018, 2020; Zhang L et al, 2018; Treumann and Baumjohann, 2019; Wang GQ et al, 2020a; Kitamura et al, 2020). Of these terms, the first two describe the observable phenomenon, while the last two emphasize the generation mechanism and nature.…”
Section: Introductionmentioning
confidence: 99%
“…These structures were first identified in the solar wind (Turner et al, 1977), and were subsequently observed frequently in the planetary magnetosheath (e.g., Cattaneo et al, 1998; Balikhin et al, 2009; Tsurutani et al, 2011; Yao ST et al, 2017), in the magnetotail (e.g., Ge YS et al, 2011; Yao ST et al, 2016; Zhang XJ et al, 2017), in the magnetospheric cusp (Shi QQ et al, 2009; Jasinski et al, 2017), and even in the magnetosphere of comets (Russell et al, 1987; Plaschke et al, 2018). They have been identified under various names according to their generation mechanisms and property features, for example, “magnetic dips”, “magnetic decreases”, “mirror modes”, and “solitary waves” (e.g., Song P et al, 1992, 1994; Baumgärtel, 1999; Lucek et al, 1999; Horbury et al, 2004; Stasiewicz, 2004; Tsurutani et al, 2011; Yao ST et al, 2018b; Tian AM et al, 2018, 2020; Zhang L et al, 2018; Treumann and Baumjohann, 2019; Wang GQ et al, 2020a; Kitamura et al, 2020). Of these terms, the first two describe the observable phenomenon, while the last two emphasize the generation mechanism and nature.…”
Section: Introductionmentioning
confidence: 99%
“…The situation seems to be similar to that of whistler-mode waves that are frequently modulated by compressional structures in the magnetosheath (e.g., Ahmadi et al, 2018;Breuillard et al, 2018;Kitamura et al, 2020;Maksimovic et al, 2001;Smith et al, 1969;Smith & Tsurutani, 1976;Y. Zhang et al, 1998) and sometimes even in the magnetosphere (Baumjohann et al, 2000;Dubinin et al, 2007;W.…”
Section: Entire Picture Of the Mirror Mode Like Structure (Compressional Ulf Wave) And Emic Wavesmentioning
confidence: 60%
“…A clear example is the whistler mode waves modulated by compressional mirror mode waves, called lion roars, that are frequently observed in the magnetosheath (e.g., Ahmadi et al., 2018; Breuillard et al., 2018; Kitamura et al., 2020; Maksimovic et al., 2001; Smith et al., 1969; Smith & Tsurutani, 1976; Y. Zhang et al., 1998). Whistler mode waves are generated in the troughs of magnetic field intensity in the compressional mirror mode waves and cannot escape from the troughs, in cases where the amplitude of the compressional mirror mode waves is large (Kitamura et al., 2020). Thus, whistler mode waves are observed by a spacecraft only in the troughs of magnetic field intensity, and this condition causes very clear modulation (on‐off) of whistler mode waves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations